Cross-Sectional Study of Thiamine Deficiency and Its Associated Risks in Emergency Care - Joseph Miller; Daniel Grahf; Hashem Nassereddine; Jimmy Nehme; Jo-Ann Rammal; Jacob Ross; Kaitlin Rose; Daniel Hrabec; Sam Tirgari; Christopher Lewandowski (Western Journal of Emergency Medicine, 2024)
Background: Growing data indicates that thiamine deficiency occurs during acute illness in the absence of alcohol use disorder. Our primary objective was to measure clinical factors associated with thiamine deficiency in patients with sepsis, diabetic ketoacidosis, and oncologic emergencies. Methods: This was an analysis of pooled data from cross-sectional studies that enrolled adult emergency department (ED) patients at a single academic center with suspected sepsis, diabetic ketoacidosis, and oncologic emergencies. We excluded patients who had known alcohol use disorder or who had received ED thiamine treatment prior to enrollment. Investigators collected whole blood thiamine levels in addition to demographics, clinical characteristics, and available biomarkers. We defined thiamine deficiency as a whole blood thiamine level below the normal reference range and modeled the adjusted association between this outcome and age. Results: There were 269 patients, of whom the average age was 57 years; 46% were female, and 80% were Black. Fifty-five (20.5%) patients had thiamine deficiency. In univariate analysis, age >60 years (odds ratio [OR] 2.5, 95% confidence interval [CI], 1.3–4.5), female gender (OR 1.9, 95% CI 1.0–3.4), leukopenia (OR 4.9, 95% CI 2.3–10.3), moderate anemia (OR 2.8, 95% CI 1.5–5.3), and hypoalbuminemia (OR 2.2, 95% CI 1.2–4.1) were associated with thiamine deficiency. In adjusted analysis, thiamine deficiency was significantly higher in females (OR 2.1, 95% CI 1.1–4.1), patients >60 years (OR 2.0, 95% CI 1.0–3.8), and patients with leukopenia (OR 5.1, 95% CI 2.3–11.3). Conclusion: In this analysis, thiamine deficiency was common and was associated with advanced age, female gender, and leukopenia.